2016
DOI: 10.1002/2015jd024360
|View full text |Cite
|
Sign up to set email alerts
|

Arctic springtime observations of volatile organic compounds during the OASIS‐2009 campaign

Abstract: Gas-phase volatile organic compounds (VOCs) were measured at three vertical levels between 0.6 m and 5.4 m in the Arctic boundary layer in Barrow, Alaska, for the Ocean-Atmosphere-Sea Ice-Snowpack (OASIS)-2009 field campaign during March-April 2009. C 4 -C 8 nonmethane hydrocarbons (NMHCs) and oxygenated VOCs (OVOCs), including alcohols, aldehydes, and ketones, were quantified multiple times per hour, day and night, during the campaign using in situ fast gas chromatography-mass spectrometry. Three canister sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 92 publications
4
19
0
Order By: Relevance
“…Here, the model was constrained to measured Br 2 , BrO, Cl 2 , ClO, O 3 , CH 4 , C 2 H 6 , and C 3 H 8 , as well as photolysis frequencies calculated using the National Center for Atmospheric Research Tropospheric UV and Visible Radiation Model (https://www2.acom.ucar.edu/modeling/ tropospheric-ultraviolet-and-visible-tuv-radiation-model) with a surface snowpack albedo of 0.9 (26). HCHO and CH 3 CHO levels in the model were constrained to previous observations near Utqia _ gvik during spring 2009 (31,60). NO x in the model was varied from 10 to 193 ppt based on measurements near Utqia _ gvik in March 2009 for days with no town influence (33).…”
Section: Methodsmentioning
confidence: 99%
“…Here, the model was constrained to measured Br 2 , BrO, Cl 2 , ClO, O 3 , CH 4 , C 2 H 6 , and C 3 H 8 , as well as photolysis frequencies calculated using the National Center for Atmospheric Research Tropospheric UV and Visible Radiation Model (https://www2.acom.ucar.edu/modeling/ tropospheric-ultraviolet-and-visible-tuv-radiation-model) with a surface snowpack albedo of 0.9 (26). HCHO and CH 3 CHO levels in the model were constrained to previous observations near Utqia _ gvik during spring 2009 (31,60). NO x in the model was varied from 10 to 193 ppt based on measurements near Utqia _ gvik in March 2009 for days with no town influence (33).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence to support that suspicion in the remote FT is provided by the concomitant PAN measurements, with the observed PAN and CH 3 CHO mutually incompatible based on their known chemistry (Millet et al, ; Staudt et al, ). Progress has been made in recent years to quantify trace levels of CH 3 CHO in pristine environments using the NCAR Trace Organic Gas Analyzer (TOGA; see more details in the supporting information, SI; Apel et al, , ; Hornbrook et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a major precursor of peroxyacetyl nitrate (PAN; Fischer et al, 2014), which affects the longrange transport of NO x (NO + NO 2 ; Singh et al, 1990). It also affects hydrogen oxide radicals (Moxim et al, 1996;Seinfeld & Pandis, 2012) and reactive halogen chemistry (Hornbrook et al, 2016;Koenig et al, 2017). High levels of CH 3 CHO have been reported in the remote marine boundary layer (MBL; Read et al, 2012;Singh et al, 2003) and the free troposphere (FT; Singh et al, 2001Singh et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported VOCs in ambient air from Arctic sites with on-line techniques, usually during short-term campaigns. Hornbrook et al (2016) utilized non-methane hydrocarbons measurements to derive time-integrated halogen mixing ratios during the OASIS-2009 campaign at Barrow, AK. Mungall et al (2018) studied the sources of formic and acetic acid at Alert, CA during the summer of 2016.…”
Section: Introductionmentioning
confidence: 99%